Activation of mGluR5 and NMDA Receptor Pathways in the Rostral Ventrolateral Medulla as a Central Mechanism for Methamphetamine-Induced Pressor Effect in Rats - Chih-Chia Lai; Chi Fang; Chung-Yi Kuo; Ya-Wen Wu; Hsun-Hsun Lin (Biomolecules, 2020)
Acute hypertension produced by methamphetamine (MA) is well known, mainly by the enhancement of catecholamine release from sympathetic terminals. However, the central pressor mechanism of the blood-brain-barrier-penetrating molecule remains unclear. We used radio-telemetry and femoral artery cannulation to monitor the mean arterial pressure (MAP) in conscious free-moving and urethane-anesthetized rats, respectively. Expression of Fos protein (Fos) and phosphorylation of N-methyl-D-aspartate receptor subunit GluN1 in the rostral ventrolateral medulla (RVLM) were detected using Western blot analysis. ELISA was carried out for detection of protein kinase C (PKC) activity in the RVLM. MA-induced glutamate release in the RVLM was assayed using in vivo microdialysis and HPLC. Systemic or intracerebroventricular (i.c.v.) administration of MA augments the MAP and increases Fos expression, PKC activity, and phosphorylated GluN1-ser 896 (pGluN1-ser 896) in the RVLM. However, direct microinjection of MA into the RVLM did not change the MAP. Unilateral microinjection of a PKC inhibitor or a metabotropic glutamate receptor 5 (mGluR5) antagonist into the RVLM dose-dependently attenuated the i.c.v. MA-induced increase in MAP and pGluN1-ser 896. Our data suggested that MA may give rise to glutamate release in the RVLM further to the activation of mGluR5-PKC pathways, which would serve as a central mechanism for the MA-induced pressor effect.